Safety of transoral surgery for oropharyngeal malignancies: An analysis of the ACS NSQIP. (31st May 2016) - Su, Henry K.; Ozbek, Umut; Likhterov, Ilya; Brant, Jason; Genden, Eric M.; Urken, Mark L.; Chai, Raymond L.
Abstract : Objectives/Hypothesis: Minimally invasive transoral surgical approaches for the resection of oropharyngeal tumors offer unique opportunities to achieve oncologically sound results while reducing treatment‐related morbidity. The objective of this study is to characterize the mortality and complication rates of transoral oncologic resections in a large, prospective, de‐identified national dataset from multiple hospitals. Study Design: Retrospective, multi‐institutional cohort study of 305 patients. Methods: The American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) datasets were accessed and examined for adult patients who underwent transoral surgical resection of oropharyngeal cancers during the years 2010 through 2013. Patient demographics, postoperative complications, and 30‐day mortality were evaluated. Results: A total of 305 patients in the 2010 to 2013 ACS NSQIP datasets met study criteria. For the 18 postoperative complications that we assessed, 24 of 305 patients developed 37 complications, representing a complication rate of 7.9%. Among all patients, the 30‐day mortality rate was 0.7%, representing two patient deaths. The presence of preoperative dyspnea, hypertension requiring medication, and an American Society of Anesthesiologists classification of 3 or 4 were significantly associated with extended hospital length of stay (LOS) (> 4 days). On multivariate analysis, hypertension was the only factor that was marginally significant with a longer LOS (odds ratio = 1.74, P = 0.057). Conclusion: Transoral resection of properly selected oropharyngeal tumors is safe, with low 30‐day morbidity and mortality. A greater understanding of the risk factors for complications following transoral surgery may improve patient selection and safety. Level of Evidence: 4. Laryngoscope, 126:2484–2491, 2016